FRI0343 Blood concentrations of complement split product ic3b and serum c3 associate with sle disease activity. (12th June 2018) - Kim, A.H.; Strand, V.; Sen, D.; Fu, Q.; Mathis, N.; Schmidt, M.; Bruchas, R.; Staten, N.; Olson, P.; Stiening, C.; Atkinson, J.
Abstract : Background: The complement system plays a central role in systemic lupus erythematosus (SLE). Since complement activation occurs during SLE flares, complement proteins are predicted to be consumed with concomitant generation of activation-derived products at a rate proportional to the degree of disease activity. However, interpretation of values may be confounded due to the unknown impact of increased acute phase production of C3 and C4, as well as in individuals with low C4 gene copy number who have persistently low serum C4. Improved detection of complement activation would enhance clinicians' ability to more readily assess SLE disease activity and promptly identify and treat flares. We hypothesise that complement split products are more sensitive measures of complement activation and better correlate with SLE disease activity. Objectives: To examine correlations between blood levels of complement split product iC3b and serum component C3 with clinically meaningful changes in disease activity in patients with SLE. Methods: 159 consecutive subjects with American College of Rheumatology or Systemic Lupus International Collaborating Clinics classified SLE were enrolled into CASTLE (C omplement A ctivation S ignatures in Syst emic L upus E rythematosus), a prospective observational study. Patients with 1–7 study visits were included in this longitudinal analysis. 48 healthy volunteers were enrolled to establish the normal reference range of iC3b/C3. Serum C3 and C4 were measured by nephelometry. Blood levels of iC3b were assessed by a lateral flow assay. SLE disease activity was monitored utilising the Systemic Lupus Erythematosus Disease Activity Index 2K Responder Index-50 instrument. Results: iC3b/C3 ratio, double-stranded (ds)DNA antibodies (Abs), and supraphysiologic prednisone dose (>7.5 mg/day) each independently correlated with SLE disease activity employing multilevel multiple logistic regression analysis. Only iC3b/C3 was significantly associated with clinically meaningful improvements in disease activity among subjects receiving supraphysiologic doses of prednisone (high disease activity). iC3b/C3 outperformed C3 and C4 levels in discriminating both active versus inactive SLE disease and major flares versus no disease activity (figure 1). Finally, iC3b/C3, dsDNA Abs, ESR, and supraphysiologic prednisone dose were independently associated with lupus nephritis, while none were associated with SLE rash. Conclusions: Blood iC3b/C3 ratio correlates with SLE disease activity and clinically meaningful improvement in disease activity. Furthermore, it discriminates between active versus inactive SLE, and major flares compared to those patients without disease activity. Acknowledgements: This research was funded/supported by Kypha, Inc. and National Institutes of Health (NIH)/National Institute of Arthritis and Musculoskeletal and Skin Diseases (NIAMS) under Award Number R21AR069833. The content is solely the responsibility of the authors and does not necessarily represent the official views of the NIH. Disclosure of Interest: A. Kim Grant/research support from: Kypha, Inc., Consultant for: Exagen Diagnostics, Inc., Speakers bureau: Exagen Diagnostics, Inc., V. Strand Consultant for: Kypha, Inc., Abbvie, Inc., Amgen, Inc., AstraZeneca plc, Bristol Myers Squibb, Celgene Corporation, EMD Serono, Inc., Genentech/Roche Holding AG, GlaxoSmithKline plc, Janssen Pharmaceutica, Eli Lilly and Company, Novartis International AG, Pfizer, Inc. and Union Chimique Belge (UCB), D. Sen: None declared, Q. Fu Consultant for: Kypha, Inc., N. Mathis Consultant for: Kypha, Inc., M. Schmidt Employee of: Kypha, Inc., R. Bruchas Employee of: Kypha, Inc., N. Staten Employee of: Kypha, Inc., P. Olson Employee of: Kypha, Inc., C. Stiening Employee of: Kypha, Inc., J. Atkinson Consultant for: Kypha, Inc., Compliment Corporation, Gemini Therapeutics, Inc., Celldex Therapeutics, Clinical Pharmacy Services, CDMI, Omeros Corporation, Achillion Pharmaceuticals, Inc., True North Therapeutics, BioMarin Pharmaceutical, Inc., Annexon Biosciences, Inc., and AdMiRx, Inc.